Bios midiático: o corpo como o limite da comunicação - Souza, Marco André Vinhas de (2006)
This thesis works with a theoretical model that displays the fundamental relations between the human communication an the mass communication. Through a communication bias this research suggests a theory view that works with the communication principles of the media system. Relating body communication media with a combination between mass communication theories and human communication theories, as between nature and culture